Desenvolvimento de métodos para determinação fluorimétrica de vitamina B2 em multivitamínicos, cervejas e vinhos usando pontos de carbono obtidos a partir de suco de limão e cebola - Monte Filho, Severino Sílvio do (2019)
This work presents a fast, simple, one-step, and low-cost approach to the preparation of fluorescent nitrogen and sulfur co-doped carbon dots (NSCDs) through heating biomass from the lemon and onion mixture, through a domestic microwave oven for only 6.0 minutes. Aiming its characterization, the structure and optical properties of NSCDs were investigated by spectroscopic techniques. NSCDs displayed excellent fluorescence stability with a high quantum yield (23.6%) and the particle size was 4.23–8.22 nm with an average diameter of 6.15 nm. And good water solubility. In addition, a linear and proportional fluorescence attenuation was observed in presence of riboflavin (RF) in the range of 0.10 to 3.00 mg L-1 of the vitamin in phosphate buffer (pH 6.9), wich is attributed to an efficient fluorescent resonance energy transfer (FRET) between the NSCDs (donor) and RF (acceptor), whose evidence is overlap between the emission spectrum of NSCDs and the absorption spectrum of RF. This phenomenon was used as the basis for a new methodology for the determination of RF in multivitamin and mineral supplements and later in alcoholic beverages beer and wines, through an automatic flow-batch system. The limits of detection and relative standard deviation for vitamin and mineral supplements were estimated to be 1.0 ng mL–1, < 2.6% and 4.0 ng mL–1 e < 3.3%, respectively. Confidence level, and recovery study shows results between 96.0% and 101%. Which once applied and compared with reference method, no statistically significant differences were observed when applying the paired t-test at a 95 %. Thus, the viability of the new method is demonstrated, which besides simplicity presents a robustness and good analytical characteristics when compared with other studies in the literature, suggesting that it is a potentially useful alternative for the determination of riboflavin in different matrices.